(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
The building of variable interval sequencies (VI) in schedules of reinforcement is based in some important parameters. This paper informs about these parameters and their origins in behavior analysis. Another purpose of this paper is to present a model, in five simple steps, to build sequencies of variable interval in a computer spreadshit, helping reserchers to build sequencies of variable interval schedules of reinforcement. The model presented in this paper also helps in building variable duration components in schedules composed by two or more simple schedules (for exemple, multiple schedules ou mixed schedules).